Distance to radiation therapy facility influences surgery type among older women with early‐stage breast cancer. (9th December 2022) - Shrestha, Pratibha; Chu, Quyen D.; Hsieh, Mei‐Chin; Yi, Yong; Peters, Edward S.; Trapido, Edward; Yu, Qingzhao; Ferguson, Tekeda; Wu, Xiao‐Cheng
Abstract: Background: Breast‐conserving surgery plus radiation (BCT) yields equivalent or better survival than mastectomy for early‐stage breast cancer (ESBC) women. However, nationwide mastectomy trends increased in recent decades, attracting studies on underlying causes. Prior research identified that long distance to the radiation treatment facility (RTF) was associated with mastectomy. Still, it is unclear whether such association applies to young and old ESBC women comparably. We sought to delineate such impacts by age. Methods: Women diagnosed with stages 0–II breast cancer in 2013–2017 receiving either BCT or mastectomy were identified from the Louisiana Tumor Registry. We assessed the association of surgery (mastectomy vs. BCT) with the distance to the nearest or nearest accessible RTFs using multivariable logistic regression adjusting the socio‐demographic and tumor characteristics. The nearest accessible RTF was determined based on patients' health insurance. For Medicaid, uninsured, and unknown insurance patients, the nearest accessible RTF is the nearest RTF owned by the government. The interaction effect of age and distance was evaluated as well. Results: Of 11, 604 patients, 46.7% received mastectomy. Compared with distance ≤5 miles to the nearest RTF, those with distance ≥40 miles or 15–40 miles had higher odds of mastectomy (adjusted (adj) OR = 1.39, 95% CI = 1.07–1.82; adj OR = 1.17, 95% CI = 1.02–1.34). To the nearest accessible RTF, the adj ORs were 1.25 (95% CI = 1.03–1.51) and 1.19 (95% CI = 1.04–1.35), respectively. Age‐stratified analysis showed the significant association ( p < 0.05) only presented among women aged ≥65, but not those aged <65 years. Conclusion: Distance to the nearest or nearest accessible RTF influences the surgery choice, especially among women in Louisiana ≥65 years with ESBC. Further understanding of factors leading to the decision for mastectomy in this age group is needed. Abstract : Distance to the radiation therapy facility significantly affects the odds of mastectomy for older women (age = 65 years), but not younger women eligible for breast‐conserving surgery plus radiation. Target interventions that assist older women in overcoming barriers to RTFs may increase the rate of breast‐conserving surgery.